Intracellular Environment and agr System Affect Colony Size Heterogeneity of Staphylococcus aureus - Häffner, Nicola; Bär, Julian; Dengler Haunreiter, Vanina; Mairpady Shambat, Srikanth; Seidl, Kati; Crosby, Heidi A.; Horswill, Alexander R.; Zinkernagel, Annelies S. (Frontiers in Microbiology, 2020)
Staphylococcus aureus cause chronic and relapsing infections, which may be difficult to treat. So-called small colony variants (SCVs) have been associated with chronic infections and their occurrence has been shown to increase under antibiotic pressure, low pH and intracellular localization. In clinics, S. aureus isolated from invasive infections often show a dysfunction in the accessory gene regulator (agr), a major virulence regulatory system in S. aureus. To assess whether intracellular environment and agr function influence SCV formation, an infection model was established using lung epithelial cells and skin fibroblasts. This allowed analyzing intracellular survival and localization of a panel of S. aureus wild type strains and their isogenic agr knock out mutants as well as a natural dysfunctional agr strain by confocal laser scanning microscopy (CLSM). Furthermore, bacterial colonies were quantified after one, three and five days of intracellular survival by time-lapse analysis to determine kinetics of colony appearance and SCV formation. Here, we show that S. aureus strains with an agr knock out predominantly resided in a neutral environment, whereas wild type strains and a agr complemented strain resided in an acidic environment. S. aureus agr mutants derived from an intracellular environment showed a higher percentage of SCVs as compared to their corresponding wild type strains. Neutralizing acidic phagolysosomes with chloroquine resulted in a significant reduction of SCVs in S. aureus wild type strain 6850, but not in its agr mutant indicating a pH dependent formation of SCVs in the wild type strain. The in-depth understanding of the interplay between intracellular persistence, agr function and pH should help to identify new therapeutic options facilitating the treatment of chronic S. aureus infections in the future.